Decreased domain size and improved crystallinity by adjusting solvent–polymer interaction parameters in all‐polymer solar cells. Issue 4 (21st November 2014) - Zhou, Ke; Liu, Jiangang; Li, Mingguang; Yu, Xinhong; Xing, Rubo; Han, Yanchun
ABSTRACT We have investigated the effect of solvent–polymer interaction on the morphology, crystallinity, and device performance of poly‐(3‐hexylthiophene) (P3HT) and poly2, 7‐(9, 9‐didodecyl‐fluorene)‐alt‐5, 5‐[4′, 7′‐bis(2‐thienyl)‐2′, 1′, 3′‐benzothia‐diaole] (PF12TBT) blend system. 3‐Hexylthiophene (3‐HT), which had the similar structural units with both donor and acceptor materials, was chosen as the solvent additive to be added into the main solvent chlorobenzene (CB), to adjust the solvent–polymer interaction. With the 3‐HT percentage increasing from 5 to 30% in CB solution, the solvent–polymer interaction between polymer and solvent molecules decreased slightly according to the calculated solubility parameters (δ) and interaction parameters (χ12). As a result, nanoscale phase‐separated and interconnected morphology with decreased domain size of both donor and acceptor was formed. Meanwhile, the order of P3HT molecule was enhanced which resulted from the extended film drying time and increased molecular planarity after incorporation of 3‐HT. The power conversion efficiency (PCE) had a gradual improvement to 1.08% as the 3‐HT percentage reached 10%, which can be attributed to the enhanced short‐circuit current (Jsc) and fill factor (FF). However, when the 3‐HT percentage exceeded 20%, the decreased Jsc and FF ultimately decreased the PCE. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 288–296